Cross-company effects of common ownership: Dealings between borrowers and lenders with a common blockholder - Gjergji Cici; Scott Gibson; Claire Rosenfeld (University of Cologne, Centre for Financial Research (CFR), 2015)
This paper investigates investment strategies that exploit the low-beta anomaly. Although the notion of buying low-beta stocks and selling high-beta stocks is natural, a choice is necessary with respect to the relative weighting of high-beta stocks and low-beta stocks in the investment portfolio. Our empirical results for US large-cap stocks show that this choice is very important for the risk-return characteristics of the resulting portfolios and their sensitivities to common risk factors. We also show that investment strategies based on betas have a natural-hedge component and a market-timing component due to the stochastic variation of betas. We construct indicators to exploit the market-timing component and show that they have substantial predictive power for future market returns. Corresponding market-timing strategies deliver large positive excess returns and high Sharpe ratios.
Keywords: D22; G21; G23; G30; 330; cross-ownership; institutional ownership; active investment; credit market interactions; syndicated lending